In Vitro Multiplication of the Ornamental Plant Sente (Alocasia melo) - Aida Muspiah; Badriansyah; Nur Indah Julisaniah (Jurnal Penelitian Pendidikan IPA, 2026)
The genus Alocasia showed high diversity, including morphological differences among approximately 60 species. One of these species was Alocasia melo, which was distributed on Borneo Island. A. melo had high aesthetic and economic value, making it popular among ornamental plant enthusiasts. However, growing A. melo naturally was challenging due to specific habitat, such as humidity, temperature, lighting, water supply, soil pH, and indoor storage to increase survival rates. To address this, tissue culture (in vitro) was used as a method for its propagation and conservation.  This study aimed to determine the effects of different nutrient components on the in vitro growth of A. melo and to find the most effective nutrient combination for its growth. The research was an experimental study with treatments including coconut water + 6-Benzylaminopurine (BAP), algae extract + BAP, coconut water, algae extract, and coconut water + algae extract on solid media. The data were analyzed descriptively, showing the number of shoots and roots in tables and figures. The results showed that the treatment with coconut water (10 mL) + BAP (1 ppm) produced the highest average number of shoots (3.75). Meanwhile, the treatment with coconut water (30 mL) resulted in the highest average number of roots (6.75).